A Novel L-Shape Ultra Wideband Chipless Radio-Frequency Identification Tag - Khaled Issa; Muhammad A. Ashraf; Mohammed R. AlShareef; Hatim Behairy; Saleh Alshebeili; Habib Fathallah (International Journal of Antennas and Propagation)
A novel compact dual-polarized-spectral-signature-based chipless radio-frequency identification (RFID) tag is presented. Specifically, an L-shape resonator-based structure is optimized to have different spectral signatures in both horizontal and vertical polarizations, in order to double the encoding capacity. Resonators’ slot width and the space between closely placed resonators are also optimized to enhance the mutual coupling, thereby helping in achieving high-data encoding density. The proposed RFID tag operates over 5 GHz to 10 GHz frequency band. As a proof of concept, three different 18-bit dual-polarized RFID tags are simulated, fabricated, and tested in an anechoic chamber environment. The measurement data show reasonable agreement with the simulation results, with respect to resonators’ frequency positions, null depth, and their bandwidth over the operational spectrum.